Mutagenicity of selected organic solvents. - Vainio, Harri; Waters, M. D.; Norppa, Hannu (Scandinavian Journal of Work, Environment & Health, 1985)
For certain organic solvents, such as benzene, vinyl chloride, styrene, technical grade trichloroethylene, and acrylonitrile, the available studies provide convincing evidence to demonstrate activity in short-term genetic assays. For a few solvents, such as phenol, vinyl toluene, ethanol, and tetrachloroethylene, the evidence is limited to a certain test system and/or test organism. For most of the solvents reviewed, studies are either lacking or they are so inadequate that no final evaluation on the mutagenic activity of the solvents can be made.